(untitled) (Iter, 2022)
Animality represents a basic referent of a polyvalent language, adaptable to the most varied discursive contexts of positive or negative sign. Animalization of characters and animal references in tragedy present a wealth of analysis that invites to focus on these issues in Euripides’s plays. This is especially remarkable in Medea and Bacchae. The playwright deploys an extreme use of this resource rich in mechanisms as well as in degrees of dramatic intensity. As an animal with the most ambiguous symbolic values, serpents have established a particular relationship with the sacred and with the origins, apart from being one of the most important chthonic creatures. The linking of Dionysus and Medea with the animal world is overwhelming. Both characters in the mythological tradition involve representations that bring them closer to wilderness and monstrosity. It is from this perspective that we propose to analyze the ophidian references to detect a series of mechanisms that operate in both works. We find a set of remissions in intimate connection with the great victimizers (Medea and Dionysus) based on certain symbolic animals and monsters that are related to these tragic characters.